Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay S.; Rajamohanan, P. R.; Reddy, D. Srinivasa; Shanmugam, Dhanasekaran (Scientific Reports, 2018)
Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume similar to 20 times more glucose, and trophozoites metabolize similar to 6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.

Recommendations for sample selection, collection and preparation for NMR-based metabolomics studies of blood - Emwas, Abdul-Hamid; Zacharias, Helena U.; Alborghetti, Marcos Rodrigo; Gowda, G. A. Nagana; Raftery, Daniel; Mckay, Ryan T.; Chang, Chung-ke; Saccenti, Edoardo; Gronwald, Wolfram; Schuchardt, Sven; Leiminger, Roland; Merzaban, Jasmeen; et al. (Metabolomics, 2025)
BackgroundMetabolic profiling of blood metabolites, particularly in plasma and serum, is vital for studying human diseases, human conditions, drug interventions and toxicology. The clinical significance of blood arises from its close ties to all human cells and facile accessibility. However, patient-specific variables such as age, sex, diet, lifestyle and health status, along with pre-analytical conditions (sample handling, storage, etc.), can significantly affect metabolomic measurements in whole blood, plasma, or serum studies. These factors, referred to as confounders, must be mitigated to reveal genuine metabolic changes due to illness or intervention onset.Review objectiveThis review aims to aid metabolomics researchers in collecting reliable, standardized datasets for NMR-based blood (whole/serum/plasma) metabolomics. The goal is to reduce the impact of confounding factors and enhance inter-laboratory comparability, enabling more meaningful outcomes in metabolomics studies.Key conceptsThis review outlines the main factors affecting blood metabolite levels and offers practical suggestions for what to measure and expect, how to mitigate confounding factors, how to properly prepare, handle and store blood, plasma and serum biosamples and how to report data in targeted NMR-based metabolomics studies of blood, plasma and serum.
Keywords: Blood; Metabolites; Metabolomics; NMR; Plasma; Serum; Standardization